ASWAJA-ORIENTED SCHOOL CULTURE AND THE FORMATION OF STUDENTS’ RELIGIOUS CHARACTER - Muhammad Rafli Salim; Fita Mustafida; Dian Mohammad Hakim (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
The implementation of Ahlusunnah wal Jamaah-based school culture is a strategic effort in forming a moderate, inclusive educational environment based on Islamic values that are rahmatan lil 'alamin. The researcher used a qualitative research method with a case study type approach at MTs Raudlatul Ulum Karangploso with the aim of analyzing the implementation of Aswaja-based school culture at MTs Raudlatul Ulum Karangploso as the main foundation in shaping the religious character of students. The results of the study show that through strong integration with the vision of the school that understands Ahlusunah wal Jamaah, the values of moderation, tolerance, and Islamic spirituality are consistently instilled in students in the aspect of school life. The implications of this research are expected that teachers can consistently and play an active role in shaping the religious character of students through the application of school culture that understands Ahlusunnah wal Jamaah, so that moderate, tolerant, and civilized Islamic values can be firmly embedded in students' daily lives.